Description of a new Amblystira (Hemiptera: Heteroptera: Tingidae) from Argentina with a key to the South American species of the genus - Montemayor, Sara I. (Zootaxa, 2010)
Amblystira Stål is a new world American genus comprising nineteen species, most of them distributed in Central and South America. Nine species have been recorded from South America, and only Amblystira silvicola Drake is known from Argentina (Drake & Ruhoff, 1965). Members of the genus are dark, the cephalic spines are generally absent or poorly developed, the hood is absent, the paranota are scarcely developed or absent as well as the lateral pronotal carinae, the discoidal area is short not reaching the middle of the hemelytra, and the costal area is slender. The only member of the genus that has been recorded as a pest is Amblystira machalana Van Duzee, commonly known as “black lacebug”, which feeds on cassava, Manihot esculenta Crantz, an important crop of South America. Arias & Belloti (2003) studied the life cycle, behavior, and damage caused by A. machalana on M. esculenta. (Guilbert, 2005) described the fifth instar of Amblystira peltogyne Drake & Hambleton.